Ecological niche define the limits of pig agroecology: a comparative review of evidence from early centres of sedentary agriculture. Issue 6 (3rd July 2019) - Robinson, Jacob
ABSTRACT: Change strategies, and the eventual abandonment of semi-domesticated and domesticated Sus scrofa is discussed in regards to increasing regional aridity in both the ancient Levant and what is now northwest China between 8, 000 BP and 4, 000 BP. A review of literature suggests a changing agroecological role of pigs, from one closely linked to production in the local ecosystem to one closely linked to production in the human social system as drying conditions created more favourable conditions for grain agriculture. The eventual abandonment of pigs as a viable agroecosystem component is discussed.